KAJIAN SISTEM PENGANGKATAN AIR TENAGA SURYA DI GUA PLAWAN, DESA GIRICAHYO, KECAMATAN PURWOSARI, KABUPATEN GUNUNG KIDUL, DI YOGYAKARTA - , CECEP SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Solar Water Pumping System (SWPS) in Plawan Cave was build in 2008 to meet the water needs of the people in Giricahyo village, Purwosari District, Gunung kidul Regency. SWPS has a capacity of 12 kWp (kilowatt peak) and was used to drive submersible pump 10 pieces. SWPS has been damaged and are not functioning since 2010. This study is aimed to assess the SWPS based on the data characteristics of each component. The scope of research are analysis of the solar panels, pumps, controllers and cabling systems. Generally, solar panels are still in good condition but the efficiency were decreasing. Measured value of efficiency at 15, 21, 22 September 2013 is about 7.10 to 10.88% from the normal efficiency that is 13.89%. Several solar panels suffered hot spot that have a significant decrease in efficiency, that is about 4.52 to 5.7%. Pump suffers strong corrosivity and scaling on the mechanical components so as to hinder the movement of the pump when used. However, the pump still has a good electrical condition. Controller suffered damage in its regulator components. Improvement of controller can only be done with a probability of 33.3%. System wiring is still in good condition although there is an increase in resistance values. Improvement recommendations to be done are: replacing solar panels that have hot spot and permanently installed solar panels at an angle of 8 o to the north. The pump must be repaired on mechanical components such as rotors, couplings and piping connections. Overcoming scaling required periodic cleaning of the pump. Controller can only be repaired about 3 pieces and the rest should be replaced. Then the wiring needs to be relocated to land with low human activity or make the lines underground. The investment cost for the repair is 127 507 000,00 IDR.